Evaluasi Penggunaan Sistem E-Kinerja (SIEKIN) Pegawai Negeri Sipil di Kabupaten Lampung Timur - Antoni Saputra; Mirnawati Mirnawati; Wahyu Widodo (Journal of Research in Social Science and Humanities, 2021)
The E-Kinerja Information System (SIEKIN) was created to store civil servant information, simplify the process of creating and setting Employee Work Targets (SKP), assessing work behavior, and creating reports automatically. This research aims to analyze and describe the evaluation of the implementation of the E-Kinerja Information System (SIEKIN) and Performance Assessment of Civil Servants (Pns) at the East Lampung Regency Education and Culture Service. Qualitative research methods using a descriptive approach were used in this research. Primary data was collected using data collection techniques in the form of interviews with informants and observations at the research location. Meanwhile secondary data is obtained through documentation. The results of the research were measured using policy evaluation indicators according to William Dunn, namely effectiveness, efficiency, adequacy, equity and responsiveness. In terms of effectiveness indicators, the implementation of SIEKIN is going well with the SIEKIN objectives being achieved. Efficiency indicators have a big impact on the speed of reporting completion. The adequacy indicator was not achieved due to the lack of supporting capacity such as difficult internet access. The indicator of equal distribution has not been achieved because there are still civil servants who are not yet able to operate the SIEKIN application. The responsiveness indicator has gone well because there are many civil servants who make their work easy.